Fighting Battles for public opinion. Print media and political discourse about the revolution in Lima and Buenos Aires (1810-1816) - Morán, Daniel (2019)
This paper identify and analyze royalists and rebels changes in visions, representations and conceptualizatios, especially with the word revolution applying historical data from Lima and Buenos Aires print media between 1810 and 1816. These changes depended on context, moment and political interest.